A unique presentation of a renal clear cell carcinoma with atypical metastases. (2015) - Staderini, F.; Cianchi, F.; Badii, B.; Skalamera, I.; Fiorenza, G.; Foppa, C.; Qirici, E.; Perigli, G.
Highlights: Management of advanced renal cancer. Role of multidisciplinary approach in atypical metastatic renal cancer. Cytoreductive surgery and metastasectomy improving effectiveness of multi-targeted therapies. Disease free progression after surgery and multi-targeted therapies in advanced renal clear cell carcinoma. Abstract: Introduction: Renal cancer is a relatively common neoplasia with renal clear cell carcinoma being the most frequent histological type. This tumor has a strong tendency to metastasize virtually to all organs. Today, new diagnostic tools allow physicians to distinguish between those patients with "incidental findings" and those with advanced metastatic disease. Presentation of case: A 70-year-old male with multiple indolent subcutaneous masses underwent colonoscopy after a positive fecal screening test for colorectal carcinoma. A rectal lesion was discovered but biopsy was negative. CT scan revealed advanced renal cancer involving the peritoneal cavity, retroperitoneum and lung. Biopsy of subcutaneous masses confirmed the suspected metastases. The patient underwent surgery (an open left nephrectomy with rectosigmoid resection and metastases debulking) because of a high risk of bowel obstruction and increasing anemia. After three years of multi-targeted therapy and follow-up, the patient is still asymptomatic and in good general condition. Discussion: Treatment of metastatic renal cancer is still controversial even if more than 30% of patients have metastasis at the time of diagnosis. Recently introduced targeted therapies are encouraging but still present problems with side effects and an unlimited period of efficacy. Although there is no consensus, several studies and guidelines consider metastasectomy to be a valid option. Conclusion: Recent series highlight surgery as a key-point in the management of advanced renal clear cell carcinoma. Our case demonstrates the validity of a surgical strategy supported by a multidisciplinary approach.